Clinical and genetic features of human metapneumovirus infection in children. Issue 1 (15th January 2016) - Park, Ji Young; Yun, Ki Wook; Lim, Jae Woo; Lee, Mi Kyung; Lim, In Seok; Choi, Eung Sang
Abstract: Background: Human metapneumovirus (hMPV) is one of the main pathogens responsible for respiratory tract infection in children. Methods: From 2011 to 2013, nasopharyngeal aspirates were obtained from Korean children and tested for hMPV on reverse transcription–polymerase chain reaction (RT‐PCR). The genotype of hMPV in each sample was identified on PCR‐restriction length polymorphism analysis of the fusion gene. We divided patients into three groups according to degree of fever. Patients with fever peaking at >39.5°C or lasting >7 days were classified as the high fever (HF) group; those with fevers peaking at <38.5°C and lasting <72 h were classified as the low fever (LF) group; and the other subjects were classified as the moderate fever group. Results: Among 457 samples positive for hMPV, hMPV genotype was able to be identified in 399 (87.3%); of these, A2a was found in 97 (24.3%), B1 in 186 (46.6%), and B2 in 116 (29.1%). Clinical features of hMPV infection were compared between the HF and LF groups. We classified 80 subjects into the HF group and 84 subjects into the LF group. Mean absolute neutrophil count (5625 ± 4418 vs 4072 ± 3076/μL, P = 0.010) and C‐reactive protein (2.39 ± 3.39 vs 0.96 ± 1.77 mg/dL, P = 0.001) were higher in the HF group. Wheezing (5.0% vs 32.1%, P < 0.001) and dyspnea (2.5% vs 15.5%, P = 0.010) were more frequently seen in the LF group. Genotype distribution was similar in the two groups. Conclusion: Two distinct clinical presentations of hMPV infection were identified in this study.